Relative Competence of the Sharia Court: Talaq Divorce Lawsuit and Protection of Women’s Rights - Darmawan, Darmawan; Suhaimi, Suhaimi; Natsir, Muhammad; T. Rasyidin, T. Rasyidin; Mustakim, Mustakim (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This paper examines how the legal protection of women in the event of talaq divorce at the Sharia Court is related to the relative competence of the Sharia Court. This study is significant due to many talaq divorce cases at the Sharia Court filed by husbands not based on the wives’ domiciles. Such practices have been contrary to the principle of civil procedural law, which stipulates that a divorce case filed by the husband must be based on the wife’s domicile. Data were taken from talaq divorce decisions tried by the Banda Aceh Sharia Court, analyzed using the principles of civil procedural law. Findings of the study revealed that the majority of talaq divorce cases tried by the Sharia Court did not have strong legal force, as they were not in line with the principle of actor sequitor forum rei. In general, the decisions of the Banda Aceh Sharia Court in talaq divorce cases were made without the presence of the respondents (wives). Such decisions not only contradicted the principles of civil procedural law, but also had an impact on limited access for women to defend their interests in the courtroom.